Analysis of Demand Elasticity and Pricing Strategy at Mcdonald’s - marlin, Revina; Vadhillaesa, Shania; Yenti, Yatna; Aristiawan, Dhani; Zefriyenni, Zefriyenni (Eduvest - Journal of Universal Studies, 2025)
The rapid development of technology has significantly influenced economic changes and consumer behavior. The economy has become more modern, driven by demand and supply, with prices shaped by the interaction between consumer demand and producer supply, forming the basis of marketing activities. One of the most competitive sectors in the food industry is the fast-food business, where pricing strategies play a crucial role in maintaining market share. This study aims to analyze price elasticity of demand and pricing strategies at McDonald's in Padang. A descriptive quantitative research method was employed, with a total sample of 94 respondents. The research findings indicate that both price elasticity of demand and pricing strategies significantly impact customer satisfaction. Effective pricing can attract more customers and enhance their loyalty, ultimately contributing to overall customer satisfaction. Understanding price elasticity of demand enables McDonald's to respond effectively to market fluctuations and changes in consumer behavior. Based on these findings, it is recommended that McDonald's continuously monitor and adjust its pricing strategies and promotional efforts to maintain and improve customer satisfaction.